–Heresy (bid’ah) an methodologies of heresy from the perspective of the two imams: ibn Taymiya and shatibi. – A comparative fundamentalist study - Shamam, Al-Bashir Mohammed (Journal of Islamic Sciences, 2019)
This paper studies the concept of heresy from the perspective of the two Imams Ibn Taymiya and Al Shatibi. It presents examples of their works on the heretics and shows the difference between heresy and unprecripted interest and approved interest, and the levels of heresy and some of the laws pertaining to them. The author has determined the characterization of heresy (bid’a) by the two Imams, that it is not of the same category in both of them , that it concerns rituals not customary behavior and he explains their method of argumentation using notions of unprescripted interest and approved one.